2014
DOI: 10.1167/iovs.14-15055
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and Agreement of Three Scheimpflug-Based Imaging Systems for Measuring Anterior Segment Parameters in Keratoconus

Abstract: Though Pentacam, Galilei, and Sirius showed repeatable measurements for Km, TCT, ACD, and pKm, repeatabilities with Pentacam and Sirius were better than those with Galilei. There were significant differences in the measurements between the three devices; hence they cannot be used interchangeably for anterior segment measurements in keratoconus patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 26 publications
(33 reference statements)
9
67
3
1
Order By: Relevance
“…This might be due to the Scheimpflug technology being used by the two imaging systems, which is consistent with an earlier report in keratoconus eyes. [11] Our results showed that the COV values determined for the fKm and sKm with Sirius were lower compared to the previous reports in healthy eyes[12] indicating a lower frequency of distribution. Fixed bias was present in all the paired comparisons in keratometry except Sirius-Pentacam, while Orbscan consistently underestimated fKm and overestimated sKm.…”
Section: Discussioncontrasting
confidence: 66%
“…This might be due to the Scheimpflug technology being used by the two imaging systems, which is consistent with an earlier report in keratoconus eyes. [11] Our results showed that the COV values determined for the fKm and sKm with Sirius were lower compared to the previous reports in healthy eyes[12] indicating a lower frequency of distribution. Fixed bias was present in all the paired comparisons in keratometry except Sirius-Pentacam, while Orbscan consistently underestimated fKm and overestimated sKm.…”
Section: Discussioncontrasting
confidence: 66%
“…The Medmont-E300 has been shown to be highly repeatable on normal corneas,15 however, unlike other topography instruments,16 it has not been verified on keratoconic corneas. The surface irregularity of keratoconic corneas has been demonstrated to reduce repeatability of topography devices 17.…”
Section: Discussionmentioning
confidence: 99%
“…For each eye, three Pentacam measurements were taken, and the average value was recorded in the database. Pentacam measurements are shown to have excellent repeatability and reproducibility 18. All measurements were based on the data from the 3.0 mm annular corneal diameter ring.…”
Section: Methodsmentioning
confidence: 99%